A study on Awareness and Opinion of Reward and Recognition Programme among Employees Working in Garment Industries at Tirupur City - Dr. D.Balamurugan; R.Rajeswari (International Journal of Engineering and Management Research, 2020)
Reward and Recognition plays a strong role in activating the employee performance in organization. It cultivates positive work environment and creates loyalty employees to organization. Values for their skills and talent must be quantified in terms of reward and recognition. Apart from financial rewards nowadays adaption of non-financial rewards and recognition motivates highly as a boosting agent to attract and retain right employees for right position at right time in organization. Objectives: To understand the awareness of reward and recognition programme among employees working in garment industries. To analyze the demographic profile of the employees. To assess the overall employee opinion about the existing reward and recognition program in the organization. To identify the employees level of satisfaction with existing reward system. To understand the current trend in labor market and necessity in studying employees opinion towards reward and recognition program. This study attempted to collect the data about opinion on current reward and recognition among employees working in garment industries. Methods/ Statistical Analysis: Descriptive research design is adapted for the study. Convenient sampling technique was applied and data was collected from 100 respondents. Findings: Majority of employees recommends that reward and recognition promotes their commitment and involvement efficiently and effectively. Nowadays awareness among employees about reward system found to be increased in successful organization. Majority of the employees interested to work only in the well-designed rewarded and recognition companies. Applications/ Improvements: This study could favor the industrialist and their managers to know about the employees opinion and found convenient to fill their needs to win competitive labor market. This study could also support the management to frame effective reward and recognition in future to increase employees job satisfaction and level of commitment.